Validasi Data Teknis Tidak sama dan Optical Distribution Poin (ODP) tidak sama dengan UIM Tools di PT TELKOM - -, Muhammad Harits Fadhila (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2024)
Abstract — At present the public's need for internet network access for voice, data and video services continues to increase, to run these services requires very high bandwidth and internet speed. Fiber To The Home (FTTH) is a telecommunications service architecture that utilizes optical network transmission media that supports transmission at bandwidth and internet speeds of up to 100 Mbps. One of FTTH component is Optical Ditributon Point,so we must equate the existing data in the field and the system .Therefore it is necessary to validate the ODP and the technical data are not the same in order to make it easier for field workers to increase internet speed. Because if validation is not carried out, what will happen is connection loss so that the internet cannot be used even though the bandwidth speed has been increased.Keywords— ODP, FTTH, technical data.